Structural adaptation of thermostable carboxylic acid reductase from Mycobacterium phlei - Basri, Rose Syuhada; Raja Abd. Rahman, Raja Noor Zaliha; Ahmad Kamarudin, Nor Hafizah; Mohamad Ali, Mohd Shukuri (Elsevier, 2022)
Thermostable enzymes are an exciting subject to study due to their fundamental and industrial importance. Via experiments and computer-aided software, the folding and stability at different temperatures of the enzyme carboxylic acid reductase (CAR) isolated from the moderate thermophilic Mycobacterium phlei (MpCAR), were studied. The 3499 bp of MpCAR with a molecular weight of 131.9 kDa was expressed in Escherichia coli BL21(DE3). The soluble MpCAR was purified using nickel sepharose affinity chromatography with 62% yield and 1.45 purification fold. Circular dichroism (CD) spectroscopy revealed that the MpCAR, dominated by coil, maintained its secondary structure content at 30, 40, and 50 °C. The predicted melting temperature was 48.05 °C. The half-life and bioconversion yield of this enzyme was also investigated at low (20 °C) and high (50 °C) temperatures. The enzyme showed similarities with carboxylic acid reductases from Nocardia iowensis, Mycobacterium marinum, and Segniliparus rugosus. These similarities helped predict the 3D molecular structure of the enzyme. Here, all-atom molecular dynamics (MD) simulations were performed at various temperatures. In terms of flexibility, all three domains of MpCAR showed that they were highly flexible at low and high temperatures. At 60 °C, the enzyme was found to possess a higher solvent accessible surface area (SASA) score as the MpCAR structure started to unfold. Additionally, the superposition between the simulated MpCAR structures with the initial structure proved that the T and R domains were more flexible and mobile than the A domain. The analyses from this study revealed that the MpCAR enzyme was most stable at higher temperatures compared to lower temperatures (10 and 20 °C). The information obtained from this study could be a valuable tool for molecular engineering of MpCAR, in the near future.